(untitled) (MMIT Proceedings, 2025)
This article explores the historical transformation of pedagogical theories under the influence of rapid technological development. It examines the shift from traditional teaching methods to innovative, technology-based approaches that emphasize personalized learning, interactivity, and accessibility. Key milestones in the evolution of pedagogy are discussed, including the digital revolution, the integration of artificial intelligence, and immersion in VR/AR environments. The article also addresses challenges such as the digital divide, ethical concerns, and the ongoing need for teacher training. This study highlights the crucial interplay between pedagogy and technology, offering insights into future directions for education in an increasingly digital world.